ANALYSIS OF THE TOLERANCE ATTITUDE OF CENTRAL ACEH SOCIETY TOWARDS RELIGIOUS DIFFERENCES - Riza, Muhammad; Mulasi, Syibran (Jurnal As-Salam, 2024)
This study aims to analyze the attitude of Central Aceh society towards religious differences. Central Aceh is a region with significant religious diversity, with the majority of the population adhering to Islam. However, religious differences can also be found within the Central Aceh society, such as Christianity, Hinduism, and Buddhism. This study employs a quantitative approach by collecting data through a survey conducted among 300 respondents representing the Central Aceh community. The survey instrument used is a reliable measurement scale of tolerance attitudes. The obtained data were analyzed using descriptive and inferential statistical methods. The analysis results show that, overall, the Central Aceh society exhibits a relatively high level of tolerance towards religious differences. The majority of respondents express respect for the right of every individual to choose and practice their own religion. However, there are several interesting findings regarding the factors influencing tolerance attitudes. Factors such as education, interreligious interaction experiences, and understanding of human rights significantly influence the tolerance attitudes of the Central Aceh society. This research contributes significantly to the understanding of tolerance attitudes in the Central Aceh community and provides insights for stakeholders, including the government and educational institutions, in developing programs that promote more inclusive and respectful tolerance attitudes among communities with different religious backgrounds. The policy implications derived from this research are expected to enhance harmony and inter-religious coexistence in Central Aceh, as well as foster sustainable social development processes.